Repositioning : a brand personality - Norlander, Terése; Unander-Scharin, Malin (2007)
Markets for consumer products and customer demand changes rapidly and therefore a company has to change in a way that meets these new demands. A repositioning process can be a great strategy for companies to change their position in the marketplace. Repositioning can affect the brand personality, and it is important that this personality features can be compared with those for humans. For this reason, the purpose of this study is to provide a deeper understanding on how customers react to a brand when it is repositioned. In order to reach this purpose, research questions focused on looking at the concerning the strategic risks and benefits with the repositioning, as well as taking a look at how a brand's personality might change during such a repositioning. Based on these research questions, a review of the relevant literature was conducted, resulting in a conceptual framework. This framework was then used to guide this study's data collection. Using a qualitative, case study approach data was collected from a focus group consisting of eight female students at Luleå University of Technology, looking at the recent repositioning of the brand Hennes and Mauritz (H&M). The findings indicate that several benefits follow with repositioning. However, it is risky for the brand if it is not conducted correctly, resulting in the company losing their creditability and their loyal customers. The findings also show that it is less risky for a more established company to go through a repositioning process than for a small-sized, not well known brand. This is for the reason that larger companies have a tendency to control the market to some extent, and have a larger amount of loyal customers. The findings also show that it is important for a company to possess a significant brand personality. The consumer has to have the ability to relate to the personality if purchasing from the specific company. It is for this reason that customers are loyal to a brand. Brand personality can change for smaller sized companies, and it is ...